A Single Grave Barrow at Harreskov, Jutland: Excavation and Pollen Analysis of a Fossil Soil - Vad, Bent; Rostholm, Hans (Journal of Danish Archaeology, 1987)
A Single Grave Barrow at Harreskov, Jutland: Excavation and Pollen Analysis of a Fossil Soil